Multispectral optoacoustic tomography of lipid and hemoglobin contrast in human carotid atherosclerosis - Karlas, Angelos; Kallmayer, Michael; Bariotakis, Michael; Fasoula, Nikolina-Alexia; Liapis, Evangelos; Hyafil, Fabien; Pelisek, Jaroslav; Wildgruber, Moritz; Eckstein, Hans-Henning; Ntziachristos, Vasilis (Photoacoustics, 2021)
Several imaging techniques aim at identifying features of carotid plaque instability but come with limitations, such as the use of contrast agents, long examination times and poor portability. Multispectral optoacoustic tomography (MSOT) employs light and sound to resolve lipid and hemoglobin content, both features associated with plaque instability, in a label-free, fast and highly portable way. Herein, 5 patients with carotid atherosclerosis, 5 healthy volunteers and 2 excised plaques, were scanned with handheld MSOT. Spectral unmixing allowed visualization of lipid and hemoglobin content within three ROIs: whole arterial cross-section, plaque and arterial lumen. Calculation of the fat-blood-ratio (FBR) value within the ROIs enabled the differentiation between patients and healthy volunteers (P = 0.001) and between plaque and lumen in patients (P = 0.04). Our results introduce MSOT as a tool for molecular imaging of human carotid atherosclerosis and open new possibilities for research and clinical assessment of carotid plaques.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiovascular disease; Carotid artery stenosis; Carotid plaque; Molecular imaging; MSOT; Photoacoustic imaging; Stroke